TECHNICAL ANALYSIS OF SECURITY AND WIRELESS LAN SOLUTION - Muhammad Yudhistira; Fivtatianti H, S.kom., MM (Jurnal Sistem Komputer, 2003)
Most of the Wireless LAN (WLAN) currently use the 2.4 gigahertz frequency band(GHz), the only part of the radio spectrum frequency (RF), which is left in the worldwho have yet to perangakat license.By using the Wireless LAN RF means that clients are located in the service accesspoint (AP) can receive data transmitted from the access point. Because radio wavespropagate through the ceiling, floor or wall, the data transmission can reach intendedrecipients who are not in the room a different building or outside the building that hasthe AP.802.11 WLAN protocol standard that has many weaknesses in terms of security. Ahacker / intruder with easy to use analysis software to identify the 802.11 Service SetIdentifier (SSID). By using these utilities, a hacker can monitor frames sent over theWLAN.Wired Equivalent Privacy (WEP) which is used to encrypt each set of frames, but ahacker can easily break the WEP encryption of information after an active networkmonitoring.